AKTIFITAS FISIK MEMPENGARUHI DAYA INGAT LANSIA - Nuraini, Novia; Putri, Pully; Batlajeri, Yomima (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
Abstract Physical Activity Affecting Elderly Cognitive Function. Declining the cognitive function is a normal situation in which elderly people usually experience. This condition might be decreased or inhibited by increasing the physical activity. The purpose of this research was to identify the relationship between physical activity and the cognitive function of the elderly. Research design used cross sectional approach with cluster sampling method on 506 elderly people. This research sample is dominated by female elderly aged 60-74 years, not graduated from junior high school/not registered in school, married status, and having chronic diseases. The results showed that there is a relationship between the level of physical activity and the cognitive function of the elderly (p=0.000; ɑ=0.05). Health promotion is expected to prevent declining cognitive function through increasing physical activity in the form of physical exercise. Moreover, the next research is expected to continue the study about the intensity, duration, frequency, and other kinds of physical exercise which are good for increasing the cognitive function for the elderly. Keyword : cognitive, elderly, physical activity